Alternative methods of normalising EMG during cycling - Albertus-Kajee, Y.; Tucker, R.; Derman, W.; Lambert, M. (Journal of Electromyography and Kinesiology, 2010)
We evaluated possible methods of normalisation for EMG measured during cycling. The MVC method, Sprint method and 70% Peak Power Output Method were investigated and their repeatability, reliability and sensitivity to change in workload were compared.